Problematika Pertimbangan Majelis Hakim Pada Putusan No. 723/Pdt.G/2021/PA.Gtlo tentang Penyelesaian Sengketa Ekonomi Syariah - Kasim, Mohamad Iksan; Salma S.; Jamaluddin, Jamaluddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2024)
This research aims to analyse the decision of the Gorontalo Religious Court Judge in filing a lawsuit regarding sharia economic disputes. The results showed that between the plaintiff and the various parties involved, all of them committed acts of default. Then, in terms of the consideration of the panel of judges, it shows that the panel of judges missed several things that should have been examined before entering the verdict reading session. The considerations presented by the panel of judges, according to the researchers, neglected one of the principles of muamalah (sharia-compliant human social interactions) in the settlement of sharia economic disputes, namely the concept of tawazun (balance). The result of this consideration is to reject the entire plaintiff's claim on the pretext of formal defects (lack of parties). As an institution that provides financing (Bank), of course, it should not neglect the Grant Deed and Deed of Encumbrance before issuing funds to be given to creditors, because the two files become the legal basis for submitting auctions if the creditor commits an act of default. Conversely, as a creditor, it is also negligent in receiving funds provided by the Bank.